Supply Chain operation Model in Digital for Curriculum Management Based on Thailand Qualifications Framework for Higher Education - Artaphon Chansamut (International Journal of Supply Chain Management, 2021)
Supply chain operation model in digital for curriculum management base on thailand qualification framework for higher education is composed of 7 main elements:  1) Raw materials 2) Suppliers 3) University 4) Finished product 5) customer 6) Satisfaction 7) Feedback.  The objective of this research was to  develop and evaluate the supply chain operation model in digital for curriculum management base on thailand qualification framework for higher education. The sample are 15  experts selected by purposive sampling. The data is analyzed by means and standardized deviations. The measurement and the evaluation of information system are based on Black-Box Testing, which is the test of total system function in order to see whether the working procedures are correct and in compliant with the desired objectives or not. The 15 experts, after evaluating the model, agreed that supply chain operation model in digital for curriculum management base on thailand qualification framework for higher education was appropriate in a good level.